Numerical study of heat transfer augmentation using pulse jet impinging on Pin Fin heat sink - Siddique, Mohd Umair; Khan, Sher Afghan; Al-Robaian, Abdulrahman; Ansari, Eman (Penerbit Akademia Baru, 2019)
Pulse jet impinging laterally on the pin fin surface have a dual effect (increment and decrement) on the heat transfer rate. The present work manifests the decrement observed in heat transfer rate because of pulse jet impinging on uniform and nonuniform dimensional pin fin heat sink compared with the steady jet. In order to justify and scale the degree of decrement in the heat transfer rate, various non-dimensional correlations for both types of the heat sink has been involved. A newly defined dimensionless number is proposed in the present work, followed by a materialistic rationalization using thermal images and flow pattern. Interpretation of the characteristic length on the target side and its effect on heat transfer rate by amending the percentage of void spaces present on it (non-uniform dimensional heat sink) is the indispensable assignment of the present research.